An assessment of the pH changes and metal ions released into artificial saliva by fake orthodontic braces - Riyam Haleem; Noor Ayuni Ahmad Shafiai; Siti Noor Fazliah Mohd Noor (BMC, 2023)
Abstract Background This present study assesses changes in the pH as well as the metal ions that fake braces release into artificial saliva (AS) using a pH meter and inductively coupled plasma atomic emission spectroscopy (ICP-AES), respectively. Methods Three sets of fake archwires (AWs) and brackets (Bs) as well as a set of controls were immersed in AS and placed in an incubator shaker at 50 rpm and 37°C. At Days 0, 1, 7, 14, 21, and 28, the pH of the AS medium was measured and 3.0 ml of AS was collected and stored at -20°C for elemental analysis. Results Significant changes in pH were observed on Days 0, 1, 7, 14, 21, and 28 in the AS of the AW group. However, these changes were only observed in the B group on Days 0 and 7. The fake samples released a large quantity of sodium (Na), potassium (K), and calcium (Ca) ions, at concentrations exceeding 100 mg/L, post-28 days of immersion. The control and fake braces samples released other ions; such as lithium (Li), magnesium (Mg), barium (Ba), chromium (Cr), copper (Cu), lead (Pb), and aluminium (Al); at concentrations that did not exceed 10 mg/L. Conclusions The pH of the AS of all the samples increased post-incubation. Only 10 ions; namely, Na, Li, K, Mg, Ca, Ba, Cr, Cu, Pb, and Al; were detected in the AS.